Knowledge, practices, and educational needs among Malaysian primary care physicians regarding childhood hearing loss - Rafidah Mazlan; Airenchara Habir (Critical Public Health)
Early identification of childhood hearing loss is crucial for optimal child development. This study investigated the knowledge, practices, and educational needs of Malaysian primary care physicians regarding childhood hearing loss. Data were collected from 76 physicians who participated in a seminar on childhood hearing loss, using a self-administered questionnaire distributed from January to February 2020, one month after the seminar. The findings revealed that 65.5% of the PCPs demonstrated adequate knowledge of childhood hearing loss. However, there were significant gaps in their understanding, particularly concerning hearing aids, cleft palate, and neonatal care implications. While about 70% of PCPs referred suspected cases promptly, the referral process often bypassed audiologists in favor of otolaryngologists, highlighting the need for standardized referral pathways. Participants also expressed a strong need for ongoing education, with the greatest interest in managing hearing problems, followed by resources for patient education and general information. Recommendations include enhancing PCP knowledge through targeted training, establishing clear referral guidelines, and providing continuous educational support to improve childhood hearing loss management in Malaysia.